Assessment of Economic Impacts of Vehicle Miles Traveled Fee for Passenger Vehicles in Nevada. Issue 1 (January 2014) - Paz, Alexander; Nordland, Andrew; Veeramisti, Naveen; Khan, Alauddin; Sanchez-Medina, Javier
This study evaluated the effectiveness and equity of a fee for vehicle miles traveled (VMT) for passenger vehicles in Nevada. In the evaluation of the fee's effectiveness, the collection capabilities, as well as the fee's impact on the number of miles users drove, were considered. Equity was evaluated by considering the impact of the VMT fee on various population groups on the basis of socioeconomics, demographics, household type, location, and ownership of fuel-efficient vehicles. To estimate the impacts on various VMT fees, a linear regression model was developed with the use of data from the 2009 National Household Travel Survey, which provided a mechanism to estimate VMT in Nevada as a function of the cost to drive, among other characteristics. The effectiveness and the equity of two alternative VMT fees were compared with the existing fuel tax system. These fees were calculated on the basis of the average fuel efficiency of vehicles in Nevada and the historical revenue from the state fuel tax. In general, a VMT fee of 3.3 cents per mile seemed to be more effective than both the existing fuel tax and a VMT fee of 2.91 cents per mile. Although the 3.3 cents per mile fee had a slightly greater impact on various population groups, its equitable distribution of the tax burden among 71.1% of households created a small average cost increase of just 0.37% per household. Thus, a 3.3 cents per mile fee would provide the necessary revenue without significantly affecting Nevada households.